(untitled) (Journal of Mathematical Study, 2022)
In this article, we will consider the Dirichlet problem for special Lagrangian equation on ΩM, where (M,J) is a compact almost complex manifold. Under the existence of C^2-smooth strictly J-plurisubharmonic subsolution u, in the supercritical phase case, we obtain a uniform global gradient estimate.